1991
DOI: 10.1113/jphysiol.1991.sp018660
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and integration in a visual pathway for circadian entrainment in the hamster (Mesocricetus auratus).

Abstract: SUMMARY1. Light-induced phase shifts of the circadian rhythm of wheel-running activity were used to measure the photic sensitivity of a circadian pacemaker and the visual pathway that conveys light information to it in the golden hamster (Mesocricetus auratus). The sensitivity to stimulus irradiance and duration was assessed by measuring the magnitude of phase-shift responses to photic stimuli of different irradiance and duration. The visual sensitivity was also measured at three different phases of the circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
2
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(191 citation statements)
references
References 49 publications
(80 reference statements)
13
173
2
2
Order By: Relevance
“…To determine whether photic entrainment may have been altered by the Clock mutation, we determined the resetting effects of single light pulses given to mice free running in constant darkness. Contrary to that seen in other nocturnal rodents (16,17), we found that short light pulses (Ͻ1 h in duration) were only weakly effective in phase-shifting circadian activity rhythms in C57BL͞6J mice. In addition, the variance of the phase shifts in the response to short-duration light pulses was high.…”
contrasting
confidence: 53%
“…To determine whether photic entrainment may have been altered by the Clock mutation, we determined the resetting effects of single light pulses given to mice free running in constant darkness. Contrary to that seen in other nocturnal rodents (16,17), we found that short light pulses (Ͻ1 h in duration) were only weakly effective in phase-shifting circadian activity rhythms in C57BL͞6J mice. In addition, the variance of the phase shifts in the response to short-duration light pulses was high.…”
contrasting
confidence: 53%
“…6). The melanopsin-based photoresponse provides the SCN with a signal that is sustained and only weakly affected by light adaptation, in line with the canonical ability of the circadian system to integrate irradiance over long time periods (Nelson and Takahashi, 1991;Dkhissi-Benyahya et al, 2007). Studies in Opn 4 Ϫ/Ϫ mice clearly demonstrate the contribution of melanopsin in photic entrainment and light-induced phase shifts (Panda et al, 2002;Ruby et al, 2002;Hattar et al, 2003;Dkhissi-Benyahya et al, 2007).…”
Section: Neuronal Response Classes In the Scnmentioning
confidence: 82%
“…This latter group conversely showed no recovery of FP elevation back to dark levels when light exposure was maintained into the subsequent night period. The magnitude of the light-induced phase advance of the circadian cycle in the late night is dependent on light intensity and on the duration of light exposure (Nelson and Takahashi, 1991;Meijer et al, 1992) and reflects a suppression of locomotor activity (Pittendrigh and Daan, 1976).…”
Section: Frequency Dependence Of Ltp Induction In the Visual Cortex Omentioning
confidence: 99%